2016
DOI: 10.1097/01.prs.0000479935.92904.a3
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness Analysis of Breast Reconstruction Options in the Setting of Postmastectomy Radiotherapy Using the BREAST-Q

Abstract: Background A consensus is lacking on a uniform reconstructive algorithm for patients with locally advanced breast cancer who require postmastectomy radiotherapy (PMRT). Both delayed autologous and immediate prosthetic techniques have inherent advantages and complications. The study hypothesis is that implants are more cost-effective than autologous reconstruction in the setting of PMRT because of immediate restoration of the breast mound. Methods A cost-effectiveness analysis model using the payer perspectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 27 publications
(21 reference statements)
1
26
0
Order By: Relevance
“…However, use of direct-to-implant reconstruction remains limited, in part, because of concerns over complication rates. 1,2 The authors’ aim was to compare 2-year complications and patient-reported outcomes for direct-to-implant versus tissue expander/implant reconstruction. …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, use of direct-to-implant reconstruction remains limited, in part, because of concerns over complication rates. 1,2 The authors’ aim was to compare 2-year complications and patient-reported outcomes for direct-to-implant versus tissue expander/implant reconstruction. …”
mentioning
confidence: 99%
“…1 Implant-based reconstruction is the most common method of postmastectomy breast reconstruction in use today. 2 Reconstructive surgeons traditionally use tissue expander/implant reconstruction with or without acellular dermal matrix and a second, later operation, for refinement of the breast pocket and implant placement. However, an alternative option is immediate placement of the implant at the time of mastectomy, referred to as direct-to-implant reconstruction.…”
mentioning
confidence: 99%
“…The generic reference to ‘breast reconstruction’ was intended to capture all articles addressing the type and timing of breast reconstruction. Two authors independently reviewed abstracts of all studies published between 1985 and 2014, and the full texts of those studies published in 2015–2017. Levels of clinical evidence (LoE) were evaluated for each publication and scored from I to V by employing Oxford criteria.…”
Section: Methodsmentioning
confidence: 99%
“…(Mastectomy with immediate breast reconstruction cost US$52 091—mastectomy alone cost US$22 334)/(mastectomy with delayed breast reconstruction cost US$92 988) = 42.12%…”
Section: Methodsmentioning
confidence: 99%